(untitled) (Journal of actual problems of jurisprudence, 2019)
The increase in guarantees of the rights and legitimate interests of the persons participating in criminal trial corresponds both to interests of the personality, and interests of society as a whole. Only at conditions of security of the rights and legitimate interests of the persons participating in criminal trial and fi rst of all accused, performance of problems of criminal legal proceedings is possible. Key words: human rights, freedom of the person, guarantee, personality, concept, legal policy, legal proceedings.